Case Report: Functional validation of a rare variant BRCA1 c.5193 + 2dupT in a family with cancer history - Dai, Guanlin; Wang, Ping; Wang, Danqing (Frontiers in Oncology, 2025)
BackgroundBRCA1 and BRCA2 genes are well-established tumor suppressors, crucial for maintaining genomic stability through their roles in DNA repair. Pathogenic variants in BRCA1/2 genes are implicated in increased susceptibility to breast and ovarian cancers. However, variant interpretation remains challenging due to the large size of BRCA1/2 (>80 kb) and the broad spectrum of variant forms, particularly for rare or recently identified variants lacking adequate population, functional or segregation data.Case presentationThis report describes a case of high-grade serous ovarian carcinoma in a patient with a strong family history of cancer. Both her mother and sister died of ovarian cancer. Genetic testing identified the germline variant BRCA1 c.5193 + 2dupT both in the patient’s tumor and peripheral blood samples, without other abnormalities detected in genomic homologous recombination deficiency assessment. Her daughter was identified as an unaffected carrier of this variant. Unfortunately, the BRCA1 status of deceased relatives could not be determined due to the unavailability of samples. Functional studies, including minigene splicing assay and transcript analysis, demonstrated that this variant induces a splicing error, specifically, an aberrant skipping of exon 18, resulting in dysfunction of the BRCA1-encoded protein. These findings provide a mechanistic explanation for the observed cancer susceptibility in this family.ConclusionThis case highlights a rare germline variant, BRCA1 c.5193 + 2dupT, in a family with a strong cancer history. In vitro functional assays confirmed that this variant induces exon 18 skipping through aberrant splicing, leading to dysfunction of BRCA1-encoded protein. To our knowledge, this is the first functional characterization of the variant BRCA1 c.5193 + 2dupT, and our data provide novel insights for risk assessment and precision treatment strategies in carriers of this variant.